Changes in lower lid position after standard phacoemulsification cataract surgery - Zamora, Maria; Marqués Fernández, Victoria; Goena, María; Montero, Cecilia; Schellini, Silvana; Khandekar, Rajiv [UNESP]; Ferreiro, Alicia (Wolters Kluwer, 2020)
Purpose: To evaluate the changes on the position of the lower lid after phacoemulsification surgery using objective methods. Methods: This prospective study evaluated the lower lid position of cataract carriers who underwent to phacoemulsification surgery from January to May 2017. Data were collected on demographics, type of anesthesia, duration of the surgical procedure, and duration of the speculum remained in place. Standardized digital photographs of the patient's face in primary gaze position were obtained preoperatively and 1, 30, 90, and 180 days, postoperatively. The data were analyzed on the distraction test, distance of the lower lacrimal punctum from the inner canthus, and margin reflex distance 2 (MRD2). Comparative and correlation statistical analyses involving preoperative and postoperative measurements were performed. Results: One hundred twelve cataract patients comprised the study sample. There were 68 (60.7%) females with a median age of 74 (interquartile range, 70-81) years old. The mean distraction test value before surgery was 7 ± 2 mm and 6.8 ± 1.8 mm 180 days postoperatively (P = 0.02). The mean lacrimal lower punctum distance changed from 5 ± 1.1 mm preoperatively to 5.4 ± 1 mm at 180 days postoperatively (P = 0.06). The mean MRD2 preoperatively was 5 ± 1 mm and increased to 5.4 ± 0.9 mm 180 days after surgery (P = 0.02). The duration of surgery and the duration that speculum remained in place were not correlated to MRD2 (P = 0.7; P = 0.98). Conclusions: There is a mild lower lid laxity after phacoemulsification reflected by slight increased lacrimal lower punctum distance to the inner canthus and MRD2. Lacrimal lower punctum distance and MRD2 vary along the study and remained altered at 180 days after surgery, while distraction test tends to recover to similar preoperative levels. Although lid laxity is common in elderly cataract carriers, even a short procedure as phacoemulsification can mildly increase flaccidity.
Keywords: Distraction test; Lacrimal lower punctum; Lid laxity; Lower lid position; Margin reflex distance; Phacoemulsification